Effects of physical activity on clinical and inflammatory markers in diagnosing multiple myeloma patients - Wang, Jiaping; Sheng, Lixia; Lai, Yanli; Ouyang, Guifang; Xu, Zhijuan (Frontiers in Physiology, 2023)
Multiple myeloma (MM) is the second most common hematological disorder. Although several drugs have been developed to treat MM, their efficacy is uncertain. In addition, how normal physical activities can decrease inflammatory responses and clinical biomarkers in MM patients needs to be better defined. Therefore, this study evaluated possible clinical and inflammatory markers to determine the early diagnosis of MM during physical activity. This study selected 30 MM patients with normal or no physical activity with ages of >50 years. This study did not require any specific exercise protocols other than noting patients’ daily life activities and considering them as physical activity for 17 days. Then, blood samples were collected to assess clinical and inflammatory markers. Regarding clinical markers, daily life activities in MM patients decreased their LDH, calcium, and β2-microglobulin levels significantly compared to other clinical biomarkers such as creatine and total protein. Further, this study observed no significant differences between daily life activities of MM patients and normal MM patients regarding levels of immunoglobulins except IgM. Furthermore, IL-6 level was significantly increased with the daily life activities of MM patients, suggesting the role of physical activities in increasing anti-inflammatory response along with altering the biochemical profiles including LDH, calcium and β2-microglobulin in MM patients.